Effects of Grilling on Total Polyphenol Content and Antioxidant Capacity of Eggplant (Solanum melongena L.). Issue 1 (14th December 2016) - Uchida, Kentaro; Tomita, Haruo; Takemori, Toshikazu; Takamura, Hitoshi
Abstract: Cooking can change the polyphenol contents of eggplant. This study elucidated the effects of grilling on total polyphenol content (TPC), antioxidant capacity, and the inner structures of eggplant. After identical hollowing, cylindrical eggplant samples were prepared and were then grilled until their center temperatures (CT) respectively reached 50, 65, 75, 85, and 95 °C. Chemical assays and observations of the inner structures clarified that TPC and 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging activity decreased as CT increased when CT was below 65 °C. Results also showed that TPC and DPPH radical scavenging activity increased as CT increased when CT was between 65 °C and 95 °C. For CT 65 °C, the samples retained polyphenol oxidase (PPO) activity up to 40% of the raw state activity. The 3 grilled eggplant models, chlorogenic acid, chlorogenic acid—sugar and chlorogenic acid—amino acid model, yielded results showing that phenol functional groups on chlorogenic acid were thermally stable and that phenol functional groups on chlorogenic acid reacted neither with sugar nor with amino acids. Results show that PPO activity is a primary reason for the decrease of the 2 indices. Optical microscopic and scanning electron microscopic observations revealed collapsed cells and inter‐tissue cracks around the surface area for CT 85 and 95 °C. Scanning electron microscopic observations clarified that intercellular bonds for CT 85 and 95 °C became thinner than those for CT 75 °C around the middle area. The phenomena explained above are reasons for the increase of TPC and DPPH radical scavenging activity.